If f ( x ) = 1 + x + x 2 + x 3 + ⋯ + x 2 0 1 7 + x 2 0 1 8 then what is f ′ ( 1 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
d x d ( 1 + x + x 2 + x 3 . . . ) = till x power 2018.
1 + 2 x + 3 x 2 + 4 x 3 . . . till the last term. substituting 1 into this, 1 power anything is just one, so f prime of 1 is just 1 + 2 + 3 + 4 + 5 . . . + 2 0 1 7 + 2 0 1 8 .
The formula for this sum is obviously 2 n ( n + 1 ) in which n is the last term. therefore the first option is the answer.
Problem Loading...
Note Loading...
Set Loading...
Given, f ( x ) = 1 + x + x 2 + x 3 + . . . + x 2 0 1 7 + x 2 0 1 8 On differentiating with respect to x , we get : f ′ ( x ) = 0 + 1 + 2 x + 3 x 2 + . . . + 2 0 1 7 x 2 0 1 6 + 2 0 1 8 x 2 0 1 7 On substituting x = 1 , we get f ′ ( 1 ) = 1 + 2 + 3 + . . . + 2 0 1 7 + 2 0 1 8 ⟹ f ′ ( 1 ) = 2 ( 2 0 1 8 ) ( 2 0 1 9 )